Pre-Viking and Early Viking Age Ribe: Excavations at Nicolajgade 8, 1985–86 - B., Lene; Jensen, Stig (Journal of Danish Archaeology, 1987)
Pre-Viking and Early Viking Age Ribe: Excavations at Nicolajgade 8, 1985–86